Charles Laurie, The Land Reform Deception: Political Opportunism in Zimbabwe's Land Seizure Era (Historia, 2021)
Charles Laurie’s book The Land Reform Deception is a welcome contribution to the debate on land reform in Zimbabwe. As the title of the book suggests, Laurie interrogates and examines the land reform process in the context of political opportunism. To construct this argument, he draws from an extensive set of primary evidence that includes wide ranging interviews with farmers and government officials, as well as surveys. He presents these in a well-argued 398-page monograph. The book is divided into ten chapters and begins with an overview of the land seizure era and concludes with an examination of the impact of the land reform on commercial agriculture production.
Keywords: Zimbabwe; ZANU PF; Charles Laurie; government